(untitled) (Gumilyov Journal of Pedagogy, 2025)
This research examines the well-being indicators of students in Western Kazakhstan, focusing on four major cities: Aktobe, Aktau, Atyrau, and Uralsk. The research employed a quantitative methodology with a cross-sectional design, involving 1,377 students aged 16-21 from leading universities in these cities. The study utilized a questionnaire based on The Global Youth Wellbeing Index and youth development index calculation methodology developed by Kazakhstan’s Ministry of Information and Social Development. The assessment covered six key domains: citizenship, economic opportunities, education, health, information and communication technologies (ICT), and security. The findings revealed an overall well-being index of 0.787 out of 1.00 across Western Kazakhstan as of August 2024, with variations among cities: Atyrau (0.809), Aktobe (0.784), Uralsk (0.780), and Aktau (0.778). The research demonstrated very high levels of well-being in education (0.84), ICT (0.83), and health (0.82) domains across all cities. Notable regional differences emerged, with Atyrau showing the highest scores in civic participation (0.79) and economic opportunities (0.83), while Aktobe led in ICT usage (0.86). The study provides valuable insights for policymakers and educational institutions to enhance student well-being and development in Western Kazakhstan.